Rare histological presentation of adenomatoid odontogenic tumor: A series of three unique cases - Bhanu Priya; Priya Kumar; Jeyaseelan Augustine; Rewa Malhotra; Aadithya B. Urs (Oral Oncology Reports)
Adenomatoid odontogenic tumor (AOT) is a benign neoplasm or hamartomatous lesion predominantly affecting females in the second decade, involving maxilla and often associated with unerupted maxillary canine, earning the epithet “two-thirds tumor”. The present case series illustrates unusual presentations of AOT including a peripheral AOT with calcifying epithelial odontogenic tumor-like areas (PAOT with CEOT-like areas), AOT associated with ossifying fibroma (AOT with OF) and AOT associated with cemento-osseous dysplasia (AOT with COD). To the best of our knowledge, PAOT with CEOT-like areas is not reported till date. Also, rarely AOT concomitant and contiguous with other odontogenic and non-odontogenic tumors such as odontoma, ossifying fibroma, cemento-osseous dysplasia have been reported in literature. Three cases of AOT with OF and two cases of AOT with COD have been documented in literature to date. Through this series, we add one case of each category and attempt to discuss its pathogenesis and prognosis.